The Effect of Episodes of Net Capital Flows on Real and Financial Sectors of the Developing Economies - Muhammad Imran; Abdul Rashid; Rashid Rauf; Muhammad Abdullah (Al-Qanṭara, 2024)
This study classifies episodes into four types, namely surge, stop, flight, and retrenchment, and investigates investigate the impact of surge, stop, flight, and retrenchment on real sector indicators (GDP growth rate, employment, and savings) and financial sector indicators (inflation, the interest rate, and domestic credit). This study adopted local projections regression to investigate the impact of episodes on the real and financial sectors of 47 developing economies over the period 1980–2018.We find that episodes have significant impacts on the real and financial sectors of the developing economies, and our findings support the notion that episodes of capital flows bring imbalances to the developing economies. We also conclude that both the liability flow-driven episode surges and the asset flow-driven flight have a stronger influence on the real and financial sectors of the developing economies as compared to stop and retrenchment. The development of the financial sector can also facilitate enhancing the strength and resilience of the developing economy in order to efficiently deal with episodes of capital inflows and outflows. This study also helps policymakers, academicians, researchers, and practitioners lift the debate to the next level on how episodes are managed for the host economy to reap the maximum benefits. To the best of the authors’ knowledge, this is the first comprehensive empirical study on the impact of episodes on real and financial sectors based on net capital flows in the context of developing economies. Keywords: Capital flows; Episodes; Local Projections